Elaboración de un manual de políticas contables para la cuenta inventarios según la NIC 2 en la empresa Siscomin Cia. Ltda. - Cepeda Flores, Katherine Jamile; Tumbaco Jimenez, Kevin Patricio (Machala : Universidad Técnica de Machala, 2024)
This research work was developed with the authorization of the company Siscomin Cía. Ltda., an organization dedicated to the sale of computers and computer services, located in the city of Machala, province of El Oro. The company began its activities on November 15, 1993 and, over the years, has experienced various challenges in the management of its inventories due to the absence of clear accounting policies. The central problem identified in the organization lies in the absence of accounting policies in the inventory account, which has generated discrepancies in the financial information, affecting the reliability of the records and making strategic decision-making difficult. To address this problem, it is proposed to prepare an accounting policy manual for the inventory account according to IAS 2 in Siscomin Cia. Ltda., and to establish adequate procedures in the storage, registration and control of stored products. The application of these accounting policies will allow for the optimization of inventory management, ensuring greater efficiency in daily operations and providing a structured guide for the correct valuation and presentation of assets in the financial statements. In addition, it will contribute to the reduction of operating costs, minimize losses due to obsolescence and guarantee adequate control over physical and accounting balances. In this way, Siscomin Cía. Ltda. will strengthen its inventory management system, improving its competitiveness and sustainability in the market.
En el presente trabajo de investigación se desarrolló con la autorización de la empresa Siscomin Cía. Ltda., una organización dedicada a la venta de computadoras y servicios informáticos, ubicada en la ciudad de Machala, provincia de El Oro. La empresa inició sus actividades el 15 de noviembre de 1993 y, a lo largo de los años, ha experimentado diversos desafíos en la gestión de sus inventarios debido a la ausencia de políticas contables claras. El problema central identificado en la organización radica en la ausencia de políticas contables en la cuenta de inventarios, lo que ha generado discrepancias en la información financiera, afectando la confiabilidad de los registros y dificultando la toma de decisiones estratégicas. Para abordar esta problemática, se propone elaborar un manual de políticas contables para la cuenta inventarios según NIC 2 en Siscomin Cia. Lta, y establecer procedimientos adecuados en el almacenamiento, registro y control de los productos almacenados. La aplicación de estas políticas contables permitirá optimizar la administración de los inventarios, asegurando una mayor eficiencia en las operaciones diarias y brindando una guía estructurada para la correcta valoración y presentación de los activos en los estados financieros. Además, contribuirá a la reducción de costos operativos, minimizará pérdidas por obsolescencia y garantizará un control adecuado sobre los saldos físicos y contables. De esta manera, Siscomin Cía. Ltda. fortalecerá su sistema de gestión de inventarios, mejorando su competitividad y sostenibilidad en el mercado.
Keywords: INVENTARIOS; POLÍTICAS CONTABLES; GESTIÓN; NIC 2